PENGARUH NILAI TAKSIRAN, KUALITAS PELAYANAN DAN LITERASI KEUANGAN SYARIAH TERHADAP KEPUTUSAN NASABAH MENGGUNAKAN JASA GADAI DI KANTOR CABANG PEGADAIAN SYARIAH BLANG PIDIE - Jaura Jaura; Suriani Suriani (Jurnal Perspektif Ekonomi Darussalam (Darussalam Journal of Economic Perspec, 2022)
The purpose of this study is to investigate the impact of estimated value, service quality, and Islamic financial literacy on customer decisions to use pawn services at the Blang Pidie Sharia Pawnshop Branch Office. The information in this study is derived from primary data collected through the distribution of questionnaires. The Slovin method was used to obtain a total sample of 97 respondents for this study using a purposeful sampling technique. The data is then analyzed using multiple linear regression methods. The findings revealed that the estimated value, quality of service, and Islamic financial literacy all had a simultaneous effect on customer decisions to use pawn services at the Sharia Pawnshop Blang Pidie Branch Office. Customers' decisions to use pawn services at the Branch Office of Blang Pidie Sharia Pawnshop are influenced positively by partially variable estimated value, quality of service, and Islamic financial literacy. Islamic financial literacy is the most influential variable. The implications are that Sharia pawnshops have a good opportunity in the world of Islamic finance, and it is expected that sharia pawnshops will be able to increase the estimated value, quality of service, and improve customer financial literacy, as well as foster a sense of public trust in Sharia pawnshops to conduct pawn transactions.